Value of The Historical Village of Segara Kembang Village as A Source of Learning Local History - Eva Dina Chairunisa; Adelia Nurtitian (Criksetra: Jurnal Pendidikan Sejarah, 2023)
In general, history learning is learning about important facts and events that occurred in the past both locally, nationally and globally. History learning has several functions, including being able to develop values ​​in students. Local history is a unit of historical study with a theme of events that are limited to a particular locality or certain area and is often known as regional history. Local history has an important function in history learning, one of which is as forming regional identity and enriching knowledge about community life patterns and regional cultural diversity in various regions. Segara Kembang Village is one of the villages located in the Ogan Komering Ulu district that has not been widely touched and used as a source of local history learning, even though this village has great potential as a source of local history learning. The aim of this research is to describe the historical values ​​found in the Segara Kembang Village settlement. The method used in this research is a qualitative descriptive method using observation, interviews and documentation. The research results show that Segara Kembang Village has values ​​that can be used as a source of local history.